Cardiovascular Therapy Benefits of Novel Antidiabetic Drugs in Patients With Type 2 Diabetes Mellitus Complicated With Cardiovascular Disease: A Network Meta‐Analysis - Saixian Shi; Xiaofeng Li; Ye Chen; Jiahao Li; Yan Dai (Journal of Diabetes)
ABSTRACT Objective Provide an evidence‐based basis for the selection of cardiovascular benefit drugs in Type 2 diabetes mellitus (T2DM) patients with cardiovascular disease (CVD). Methods Conduct a comprehensive search of all relevant literature from PubMed, Embase, Web of Science, Cochrane Library, and Clinical Trials.gov from their establishment until December 13, 2023, and select randomized controlled trials (RCTs) that meet the pre‐established inclusion and exclusion criteria. Use the Cochrane bias risk assessment tool to evaluate the quality of the included literature. Use R 4.3.2 software to conduct network meta‐analysis for drug category comparison. Results A total of 24 large‐scale randomized controlled trials (RCTs) were included, including 19 intervention measures, and 172 803 patients participated in the study. The results of the network meta‐analysis show that: GLP1RA (OR 0.89, 95% CI 0.81–0.97) and SGLT2i (OR 0.91, 95% CI 0.83–0.99) can reduce the occurrence of major adverse cardiovascular events (MACE), GLP1RA (OR 0.88, 95% CI 0.79–0.97) and SGLT2i (OR 0.89, 95% CI 0.81–0.99) reduced the risk of cardiovascular death. SGLT2i (OR 0.68, 95% CI 0.62–0.75) reduced the occurrence of hospitalization for heart failure, GLP1RA (OR 0.88, 95% CI 0.81–0.97) and SGLT2i (OR 0.89, 95% CI 0.80–0.97) reduced the occurrence of all‐cause death. Conclusion In the comparison of new hypoglycemic drug classes, GLP1RA and SGLT2i reduced MACE, cardiovascular mortality and all‐cause mortality in T2DM patients with CVD, with no significant difference in efficacy, and DPP4i was noninferior to placebo. Only GLP1RA reduced the risk of nonfatal stroke, and only SGLT2i reduced the risk of HHF.